An exploratory study of factors affecting the acquisition method of construction equipments and machineries among G7 contractors - Azizul Ridhuan, Wahid (2015)
Today contractors confront more than create, buying and construct in project construction. Contractors participate in various factors during dealing in buying or renting the equipment. As contractor, they must know how to budgeting with the capital they have with choosing the best to acquisition the equipment they want to have .This study examines the factors affecting the acquisition method of construction equipment and machinery among G7 contractors with the barriers and the problem solving for the barrier. Through 15 in-depth interviews and utilizing the constant comparative method of analysis, themes were identified including factor affecting the acquisition, barrier and also the problem solving. Price of machine as a reason for contractor to rent only emerged as a theme that was echoed by many of those interviewed. Whether it was the brand name of the machine or where the machines have much functionality made it become more expensive. Varieties of methodology are used to achieve the objectives, such as the literature review that give explanation of construction equipment and factor of acquisition.Participants’ share all their experiences including give some advice and strategy to new start-up contractor during the interview. These situation need the intelligence of project manager to determine the most appropriate construction equipment used in the project. In addition, themes that emerged in the data included: how can contractor accept and reject offered the price of the machine by the company.